Development of a defined autochthonous starter through dissecting the seasonal microbiome of broad bean paste. (30th September 2021) - Jia, Yun; Niu, Cheng-Tuo; Zheng, Fei-Yun; Liu, Chun-Feng; Wang, Jin-Jing; Lu, Zhen-Ming; Xu, Zheng-Hong; Li, Qi
Highlights: Environmental variables lead to seasonal distribution of microbiota in broad bean paste production. Seasonal distribution of microbiota results in the inconsistency of broad bean paste quality. Lactobacillales contributed to higher acidity and amino acid nitrogen in winter pei . Saccharomycetales benefited to volatile flavor substances formation in autumn pei . Co-culture of W. confusa and Z. rouxii contributes to BBP production standardization. Abstract: Bean-based fermentation foods are usually ripened in open environment, which would lead to inconsistencies in flavor and quality between batches. The physicochemical metabolism and microbial community of seasonal broad bean paste (BBP) were compared to distinguish discriminant metabolites and unique taxa, as well as their specific reasons for different flavor and quality in this study. Here, we found that environmental variables led to the seasonal distribution of microbiota, and differential microorganisms further contributed to the inconsistency of flavor quality, in which Lactobacillales was responsible for the higher titratable acid and amino acid nitrogen concentration in winter pei, while Saccharomycetales benefited the formation of volatile flavor substances in autumn pei . Additionally, we compared the effect of different combinations of Lactobacillales with Zygosaccharomyces rouxii on the quality of BBP, and found that W . confusa was more suitable for BBP fermentation rather than T . halophilus in terms of sensory characteristics and physicochemical metabolites.